Progress and Challenges for Canadian Female Physicists - Perimeter Institute (Perimeter Institute, 2011)
In recent years there has been an increase in the number of women in all academic levels in physical and applied sciences in Canada. Despite the modern feminist movement the number of women in physics continues to be less than the number of men, particularly in higher and leadership positions. As there is no rational reason for women to trail men in achieving new scientific discoveries or excel in academic teaching, the cause of this is attributed to existing gender biases in the perception and practice of science. Thus increasing the number of women in physics as well as emphasising their relevance in physics has emerged as a women